Saimnieciskās darbības novērtējums transporta nozares uzņēmumiem Latvijā - Ozoliņa, Līga (Latvijas Universitāte, 2012)
Darbs profesionālā maģistra grāda iegūšanai: 84 lapas, 14 attēli, 24 .tabulas, 44 izmantotās literatūras un citi informācijas avoti, 6 pielikumi. Darba mērķis novērtēt saimniecisko darbību Latvijas transporta nozares uzņēmumiem veikt problēmu analīzi un sniegt priekšlikums problēmu risināšanā. Darbs sastāv no 3 nodaļām. Pirmajā nodaļā pētīti kravu transporta nozare Baltijas valstīs : dzelzceļa kravu pārvadājumi, sauszemes kravu pārvadājumi, loģistika un citi pakalpojumi, investīcijas Latvijas transporta nozarē, transporta nozares attīstība ES. Otrajā nodaļā analizēti kravu pārvadājumu efektivitātes rādītāji, pakalpojuma raksturojums un dzīves cikls, pētītas kravu pārvadājumu problēmas un meklēti risinājumi. Trešā nodaļā novērtēta trīs lielāko transporta uzņēmumu saimnieciskā darbība aprēķinot realizācijas rentabilitātes, likviditātes rādītājus veikta SVID analīze. Noslēgumā izdarīti secinājumi un izteikti priekšlikumi par analizējamās nozares uzņēmumu finansiālo stāvokli un tā darbības attīstības un efektivitātes novērtējumu. Darbā pielietotas metodes ir ekonomiskās, statistiskās (salīdzināšanas, grupēšanas, grafiskās u.c.) analīzes un apraksta metodes. Atslēgvārdi: Kravu pārvadājumi, sauszemes kravu pārvadājumi, dzelzceļa kravu pārvadājumi, jūras kravu pārvadājumi, saimnieciskās darbības novērtējums, rentabilitātes analīze.

Volume of work for a professional Master's degree : 83 pages, 13 figures, 12. tables 44 used literature and other sources of information 6 appendixes Aim of the work: to assess the economic activities of Latvian transport industry for problem analysis and make suggestions to solve the problems. Paper consists of 3 parts. In the first part there is a research of transport sector in Baltic countries as well as railway transit, cargo transport, logistics and other services, investment in Latvian transport field, development of the transport in EU. In the second part of the paper there is analysis of effectiveness results of shipping, description of service and life cycle, researched shipping problems and findings of solutions. In the third part there is evaluation of three the biggest shipping enterprises economic activity by calculating realization, profitability, liquidity results, SWOT analysis. In conclusion, draws conclusions and makes suggestions about the analytic branch in the sector of financial condition and work development and assessment of effectiveness. Work methods are applied to economic, statistical (comparison, grouping, graphics, etc.) and describe the methods of analysis. Keywords: freight forwarding, road freight, rail freight, sea freight, economic,performance,cost-benefit,analysis. Volume of work for a professional Master's degree : 83 pages, 13 figures, 12. tables 44 used literature and other sources of information 6 appendixes Aim of the work: to assess the economic activities of Latvian transport industry for problem analysis and make suggestions to solve the problems. Paper consists of 3 parts. In the first part there is a research of transport sector in Baltic countries as well as railway transit, cargo transport, logistics and other services, investment in Latvian transport field, development of the transport in EU. In the second part of the paper there is analysis of effectiveness results of shipping, description of service and life cycle, researched shipping problems and findings of solutions. In the third part there is evaluation of three the biggest shipping enterprises economic activity by calculating realization, profitability, liquidity results, SWOT analysis. In conclusion, draws conclusions and makes suggestions about the analytic branch in the sector of financial condition and work development and assessment of effectiveness. Work methods are applied to economic, statistical (comparison, grouping, graphics, etc.) and describe the methods of analysis. Keywords: freight forwarding, road freight, rail freight, sea freight, economic,performance,cost-benefit,analysis.
Economic assesment of Latvian transport industry bussiness
Keywords: Ekonomika